WAYS TO IMPROVE MANAGEMENT IN DIGITAL TOURISM - Radjapova Nasiba Makhmudjonovna (Ecominds Press, 2025)
This article analyzes the ways to improve digital tourism management, its possibilities. Through the development of digital platforms, artificial intelligence, data analytics and online reservation systems, it is possible to optimize management processes in the tourism sector. These approaches will help make tourism more competitive, efficient and customer-oriented.
Keywords: Digital marketing, ICT sector, analytics.